Using creative drama to teach history to primary school students / Haneem Said - Said, Haneem (2015)
Young Malaysians today show little interest in remembering historical events, issues of governance and tend to treat patriotism trivially. These issues occur because most students are generally taught to memorise historical facts, rather than appreciate or understand History. This research investigates the used of creative drama in History teach ing and the main creative drama strategies that helps to increase students' scores in History test. The students were divided into two groups: The control group and the experimental group. The control group used textbooks and the "chalk and talk' approach, while the experimental group was exposed to the creative drama method for History classes. Data collections were made through a set of pre-post objective questions test and reflective journal. The data were analysed using aT-test and content analysis technique. The outcomes of this research show that the scores of students in both groups increased. However, the experimental group achieved a more progressive development with the mean score increasing by 17.49 (p< .05) compared to the control group which only increased by 6.18 (p< .05). These findings were supported by content analysis of the samples" reflective journals which found that theatre games can be used as a main strategy to helps students understands History and to improve their achievement in learning this subject in primary school.